2020
DOI: 10.1037/pspi0000223
|View full text |Cite
|
Sign up to set email alerts
|

Food restriction and the experience of social isolation.

Abstract: Across 7 studies, food restrictions increased loneliness by limiting the ability to bond with others through similar food consumption. We first found that food restrictions predict loneliness using observer- and self-reports among children and adults (Studies 1–3). Next, we found mediation by the experience of worry and moderation by eating similar food as others. When restricted individuals were unable to bond over a meal (i.e., they ate different vs. the same food as others), they worried. These “food worrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 76 publications
(91 reference statements)
1
18
0
1
Order By: Relevance
“…To normalise behaviour around food, parents need to be vigilant, yet guard against inadvertently creating an environment of fear, as this can impact self-confidence in their children and lead to social withdrawal and abnormal eating patterns. 6 , 7 One starting point is to improve health literacy across the community to engender support and awareness as health messages can influence behaviour. 5 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…To normalise behaviour around food, parents need to be vigilant, yet guard against inadvertently creating an environment of fear, as this can impact self-confidence in their children and lead to social withdrawal and abnormal eating patterns. 6 , 7 One starting point is to improve health literacy across the community to engender support and awareness as health messages can influence behaviour. 5 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…This is particularly relevant in the context of nutrition interventions due to the social and emotional significance of food [94]. It is critical to consider that adhering to new dietary and/or lifestyle restrictions can be isolating, contributing to loneliness and acting as a barrier to socialisation [95]. Therefore, it is essential that clinical trials monitor patient-reported life impact outcomes such as social and emotional wellbeing to accurately assess the long-term sustainability and appropriateness of such interventions [96].…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is the unpleasant feeling of social isolation, which occurs when social needs are not adequately met (Hawkley and Cacioppo 2007;Russell, Peplau, and Cutrona 1980;Wang, Zhu, and Shiv 2012;Weiss 1973). It is a subjective experience (Ponzetti 1990;Waytz et al 2015), sometimes caused by (and operationalized as) objective social exclusion (e.g., Woolley, Fishbach, and Wang 2020). Though, notably, social exclusion has effects beyond loneliness (e.g., increases avoidance motivation [Han, Duhachek, and Rucker 2015], increases the motivation to differentiate oneself from others [Wan, Xu, and Ding 2014]).…”
Section: Loneliness and The Desire To Connectmentioning
confidence: 99%